Meticulous and Early Understanding of Congenital Cranial Defects Can Save Lives - Ali Al Kaissi; Sergey Ryabykh; Farid Ben Chehida; Hamza Al Kaissi; Susanne Gerit Kircher; Franz Grill; Alexander Guben (MDPI AG, 2023)
Background: Omitting the early closure of the cranial sutures in newly born children is not an uncommon practice. We describe the natural history of several unrelated children and adults from two unrelated families. These children were born with variable clinical manifestations: craniofacial asymmetry, ocular proptosis, floppiness, and progressive deceleration in cognitive development. None of these children underwent a cranial sutures assessment. False diagnoses of positional plagiocephaly, neonatal thyrotoxicosis, congenital muscular atrophy, and hydrocephalus were given to the parents. This sort of malpractice was the reason behind a sequence of devastating pathological events that occurred in the lifetime of these children and adults. Material and Methods: This was a multigenerational study of two unrelated families. In total, we studied three children (aged 7-19 years) and three adults (aged 40-52 years) from two families. The children from the first family were referred to our departments because of pre-pubertal scoliosis, kyphoscoliosis, and early-onset osteoarthritis. Reading the clinical histories of these children signified apparent clinical misconceptions. For instance, craniofacial asymmetry was misinterpreted as positional plagiocephaly and treated by means of helmet molding therapy. Ocular proptosis was given the false diagnosis of neonatal thyrotoxicosis. Floppiness (hypotonia) was misdiagnosed as congenital muscular dystrophy. The index case from the second family showed progressive deceleration in his cognitive development, associated with signs of increased intracranial pressure. The only diagnosis was Dandy-Walker malformation. We documented every patient in accordance with the clinical and radiological phenotypic characterizations. The genotype characterization followed accordingly. Results: All patients in family (I) manifested a phenotype consistent to a certain extent with the clinical phenotype of Shprintzen-Goldberg syndrome (SGS), though the intensity of spine deformities was greater than has been described in the literature. The second family showed a constellation of Marfanoid habitus, craniosynostosis, increased intracranial pressure, hydrocephalus, Dandy-Walker malformation, seizures, and intellectual disability. The overall clinical phenotype was consistent but not fully diagnostic of craniosynostosis-Dandy-Walker-malformation hydrocephalus syndrome. The early closure of the sutures was totally different from one patient to another, including the premature closure of the metopic, coronal, squamosal, and sagittal sutures. One patient from family (II) underwent the implementation of a shunt system at the age of 3 years, unfortunately passing over the pre-existing craniosynostosis. In addition to skeletal deformities, a history of seizures and severe intellectual disability was recorded. The proband underwent chromosomal karyotyping, the FISH test, and whole-exome sequencing. Conclusion: The purpose of this study was fivefold. Firstly, to gain a meticulous understanding in order to differentiate between positional plagiocephaly, hypotonia, and congenital exophthalmos and their connections to abnormal craniofacial contours was and still is our first and foremost concern. Secondly, we aimed to characterize craniosynostosis, seizures, intellectual disabilities, and hydrocephalus associated with Marfanoid habitus, which were clearly demonstrated in our patients. Thirdly, we aimed to address the imperative for interpretations of clinical and radiological phenotypes and relate these tools to etiological understanding, which is an essential basis for diagnosis in the majority of long-term pediatric admissions. Fourthly, we aimed to assess the impacts of the missed early closure by the pediatricians and pediatric neurologists, which added a heavy pathological burden on these patients and their families. Fifthly, we aimed to identify whether early and diligent recognition can assist in cranial vault remodeling via surgical intervention to halt premature cranial suture fusions and can possibly alter the devastating course and the complications of the synostosed sutures.